Modern aspects of diagnosis and treatment of obliterating atherosclerosis of the lower extremities - V. V. Skvortsov; A. V. Sabanov; A. A. Eremenko (Лечащий Врач)
Currently, diseases of the arteries of the lower extremities are an urgent problem of modern medicine, one of the most common variants of peripheral artery diseases. Of these, obliterating atherosclerosis of the lower extremities and, as a consequence, intermittent lameness deserve special attention. Intermittent claudication is one of the main and striking symptoms of diseases of the arteries of the lower extremities, the main cause of disability, has a significant negative impact on the quality of life of the patient. In 60% of cases, it is possible to accurately establish the diagnosis using general clinical research methods (analysis of patient complaints, history taking, examination, palpation, auscultation, functional tests). On examination, it is necessary to pay attention to the color of the skin of the affected limbs, the presence of hairline, the condition of the nail plates. Palpation allows you to determine the pulsation at standard points (femoral triangles, popliteal fossae, posterior surfaces of the medial condyles of the tibia, dorsal surfaces of the feet), thereby revealing the level of damage to the arteries of the lower extremities. Auscultation also allows you to determine the level of damage to the arteries of the lower extremities – a systolic murmur will be heard over the stenotic artery. Functional tests include Oppel's symptom of plantar ischemia, Goldflam and Samuels's test, Goldflam's test, Sitenko – Shamova's test, Panchenko's knee phenomenon. To date, the vascular endothelium is considered an active endocrine organ that supports vascular hemostasis, due to the synthesis and isolation of biologically active compounds. This fact has found application in the diagnosis and treatment of this group of diseases. Despite the extensive range of medications, special attention is paid to cilostazol and alprostadil. In the case of insufficient effectiveness of drug treatment, it is necessary to resort to surgical intervention using the most rational method in this case. Lifestyle modification and physical activity play an important role in the treatment, which is confirmed by the results of research.